Meningkatkan hasil belajar servis atas menggunakan pembelajaran problem based introduction (PBI) dalam permainan bolavoli pada siswa kelas VIII di SMP negeri 15 mataram - Nur Maulidiya; Soemardiawan; Rindawan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The problem in this research is the lack of interest of students in participating in physical education lessons students feel bored or fed up with the material taught by the teacher because the teacher only provides basic material without games. The aim to be achieved in this research is to improve service learning outcomes using Problem Based Introduction (PBI) learning volleyball for class VIII students at SMP Negeri 15 Mataram. The research method is classroom action research carried out in two cycle, each cycle consisting of planning, implementation, observation and reflection. The population in this study were 11 students who were in class VIII at SMP Negeri 15 Mataramand the sample used in this study was purposive sampling because the sample chosen by the researcher specifically or deliberately chose one class based on the research objectives which were considered representative. The sample in this study was class VIII A students at SMP Negeri 15 Mataram. Data collection techniques were by observation and assessment of the results of learning to service volleyball. The data analysis technique used inthis result is descriptive qualitative with persentage results. Based on the result of data analysis in cycle I, it was found that 11 students (34.37%) had completedtheir studies and 21 students (65.62%) had not yet completed their studies and the result of the second cycle II test showed that 28 students (87.5%) had completed their studies and 4 students (12.5%) have not completed their studies.